(3GdQSGdI GdTQajI aj GdfSH GdJCdjajIs - (3YHO GdeDef Hf jhSa Hf aGNQ GdNhjj GdCQehj GdHZOGOj, Uaj GdOjf,J (B693 (3g` s
(3ChdgG (B:s
(3gPg QSGdI JTJed Ydi Yde GdfSH GdJCdjajI s
(3BNQgG (B:s
(3hJMJ cd fZeI GYOGO HGdQehR GdgfOjI s
(3HgG fXGe GdJYbjHIs
(3fSNI SGOSIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B170 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B198s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3ehSjbi JjehQ (B2) s
Keywords: (3GdehSjbi hGdZfGAs